An update on the pharmacological management and prevention of cerebral edema: current therapeutic strategies. (24th May 2021) - Pergakis, Melissa; Badjatia, Neeraj; Simard, J. Marc
ABSTRACT: Introduction : Cerebral edema is a common complication of multiple neurological diseases and is a strong predictor of outcome, especially in traumatic brain injury and large hemispheric infarction. Areas Covered : Traditional and current treatments of cerebral edema include treatment with osmotherapy or decompressive craniectomy at the time of clinical deterioration. The authors discuss preclinical and clinical models of a variety of neurological disease states that have identified receptors, ion transporters, and channels involved in the development of cerebral edema as well as modulation of these receptors with promising agents. Expert opinion : Further study is needed on the safety and efficacy of the agents discussed. IV glibenclamide has shown promise in preclinical and clinical trials of cerebral edema in large hemispheric infarct and traumatic brain injury. Consideration of underlying pathophysiology and pharmacodynamics is vital, as the synergistic use of agents has the potential to drastically mitigate cerebral edema and secondary brain injury thusly transforming our treatment paradigms.